Bone metabolism in Langerhans cell histiocytosis. Issue 7 (July 2018) - Anastasilakis, Athanasios D; Tsoli, Marina; Kaltsas, Gregory; Makras, Polyzois
Abstract : Langerhans cell histiocytosis (LCH) is a rare disease of not well-defined etiology that involves immune cell activation and frequently affects the skeleton. Bone involvement in LCH usually presents in the form of osteolytic lesions along with low bone mineral density. Various molecules involved in bone metabolism are implicated in the pathogenesis of LCH or may be affected during the course of the disease, including interleukins (ILs), tumor necrosis factor α, receptor activator of NF-κB (RANK) and its soluble ligand RANKL, osteoprotegerin (OPG), periostin and sclerostin. Among them IL-17A, periostin and RANKL have been proposed as potential serum biomarkers for LCH, particularly as the interaction between RANK, RANKL and OPG not only regulates bone homeostasis through its effects on the osteoclasts but also affects the activation and survival of immune cells. Significant changes in circulating and lesional RANKL levels have been observed in LCH patients irrespective of bone involvement. Standard LCH management includes local or systematic administration of corticosteroids and chemotherapy. Given the implication of RANK, RANKL and OPG in the pathogenesis of the disease and the osteolytic nature of bone lesions, agents aiming at inhibiting the RANKL pathway and/or osteoclastic activation, such as bisphosphonates and denosumab, may have a role in the therapeutic approach of LCH although further clinical investigation is warranted.